Young at Heart: Pioneering Approaches to Model Nonischaemic Cardiomyopathy with Induced Pluripotent Stem Cells - Aoife Gowran; Marco Rasponi; Roberta Visone; Patrizia Nigro; Gianluca L. Perrucci; Stefano Righetti; Marco Zanobini; Giulio Pompilio (Stem Cells International)
A mere 9 years have passed since the revolutionary report describing the derivation of induced pluripotent stem cells from human fibroblasts and the first in-patient translational use of cells obtained from these stem cells has already been achieved. From the perspectives of clinicians and researchers alike, the promise of induced pluripotent stem cells is alluring if somewhat beguiling. It is now evident that this technology is nascent and many areas for refinement have been identified and need to be considered before induced pluripotent stem cells can be routinely used to stratify, treat and cure patients, and to faithfully model diseases for drug screening purposes. This review specifically addresses the pioneering approaches to improve induced pluripotent stem cell based models of nonischaemic cardiomyopathy.